Fear of falling in older adults living at home: associated factors - Luciano Magalhães Vitorino; Carla Araujo Bastos Teixeira; Eliandra Laís Vilas Boas; Rúbia Lopes Pereira; Naiana Oliveira dos Santos; Célia Alves Rozendo
Abstract OBJECTIVE To identify the factors associated with the fear of falling in the older adultliving at home. METHOD Cross-sectional study with probabilistic sampling of older adultenrolled in two Family Health Strategies (FHS). The fear of falling was measured by the Brazilian version of the Falls Efficacy Scale-International and by a household questionnairethat contained the explanatory variables. Multiple Linear Regression using the stepwise selection technique and the Generalized Linear Models were used in the statistical analyses. RESULTS A total of170 older adultsparticipated in the research, 85 from each FHS. The majority (57.1%) aged between 60 and 69; 67.6% were female; 46.1% fell once in the last year. The majority of the older adults(66.5%) had highfear of falling. In the final multiple linear regression model, it was identified that a higher number of previous falls, female gender, older age, and worse health self-assessment explained 37% of the fear of falling among the older adult. CONCLUSION The findings reinforce the need to assess the fear of falling among the older adultliving at home, in conjunction with the development and use ofstrategies based on modifiable factors by professionalsto reduce falls and improve health status, which may contribute to the reduction of the fear of falling among the older adult.